Comparing neuromotor functions in 45- and 65-year-old adults with 18-year-old adolescents - Kakebeeke, Tanja H.; Chaouch, Aziz; Caflisch, Jon; Eichelberger, Dominique A.; Wehrle, Flavia M.; Jenni, Oskar G. (Frontiers in Human Neuroscience, 2023)
This cross-sectional analysis investigates how neuromotor functions of two independent cohorts of approximately 45-and 65-year-old individuals are different from 18-year-old adolescents using the Zurich Neuromotor Assessment-2 (ZNA-2).A total of 186 individuals of the Zurich Longitudinal Studies (ZLS) born in the 1950s (mean age 65.1 years, SD = 1.2 year, range of ages 59.0-67.5 years, n = 151, 82 males) and 1970s (mean age 43.6 years, SD = 1.3 year, range of ages 40.8-46.6 years, n = 35, 16 males) were tested with the ZNA-2 on 14 motor tasks combined in 5 motor components: fine motor, pure motor, balance, gross motor, and associated movements. Motor performance measures were converted into standard deviation scores (SDSs) using the normative data for 18-year-old individuals as reference.The pooled motor performance of the 45-year-old individuals was remarkably similar to that of the 18-year-olds (SDS from -.22 to 0.25) apart from associated movements (-0.49 SDS). The 65-year-olds showed lower performance than the 18-year-olds in all components of the ZNA-2, with the smallest difference observed for associated movements (-0.67 SDS) and the largest for gross motor skills (-2.29 SDS). Higher body mass index (BMI) was associated with better performance on gross motor skills for 45-year-olds but with worse performance for 65-yearolds. More educational years had positive effects on gross motor skills for both ages.With the exception of associated movements, neuromotor functions as measured with the ZNA-2 are very similar in 45-and 18-year-olds. In contrast, at age 65 years, all neuromotor components show significantly lower function than the norm population at 18 years. Some evidence was found for the last-in-first-out hypothesis: the functions that developed later during adolescence, associated movements and gross motor skills, were the most vulnerable to age-related decline.